Knowledge, attitude, and practice regarding charcoal consumption among households in Sanaag province, North-Eastern Somalia - Yusuf, Faiza Ali; Mohd Kusin, Faradiella; Kpalo, Sunday Yusuf (MDPI AG, 2021)
Charcoal consumption is prevalent in the Sanaag province of North-Eastern Somalia amidst the energy crisis, leading to destruction of the fragile environment and negative impacts on citizen’s health. This study seeks to evaluate charcoal consumption trends among households. The objectives were to assess the households’ level of knowledge, attitude, and practice (KAP) regarding charcoal consumption, and to determine the association of knowledge and attitude with practices. A questionnaire was designed and distributed to 343 households who were selected using a multistage random sampling technique. Data were analyzed by both descriptive and inferential statistics using SPSS. Findings showed that 79.3% of the respondents have a good level of knowledge, 63.6% have fair level of attitude, and a fair level of practice was displayed by 77.3%. A significant association was found of charcoal consumption practices with knowledge, but not with attitude. Results also suggest that good knowledge does not necessarily translate into good practice. Improving knowledge and attitude through appropriate intervention programs or policies can ensure sustainable charcoal consumption practice. This study is a substantial contribution to the literature on KAP relating to charcoal consumption among households in Somalia.